2017
DOI: 10.1098/rspb.2017.0176
|View full text |Cite
|
Sign up to set email alerts
|

The ‘male escape hypothesis’: sex-biased metamorphosis in response to climatic drivers in a facultatively paedomorphic amphibian

Abstract: ResearchCite this article: Mathiron AGE, Lena J-P, Baouch S, Denoël M. 2017 The 'male escape hypothesis': sex-biased metamorphosis in response to climatic drivers in a facultatively paedomorphic amphibian. Paedomorphosis is a major evolutionary process that bypasses metamorphosis and allows reproduction in larvae. In newts and salamanders, it can be facultative with paedomorphs retaining gills and metamorphs dispersing. The evolution of these developmental processes is thought to have been driven by the costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…They raise interesting questions about the evolutionary pathways that contribute to the diversification of movement strategies in the wild (Cote et al 2017b): is dispersal only a by-product of the evolution of migratory movement providing temporary escape from the environmental constraints of the aquatic habitat (e.g. predation and drying up: Winandy et al 2015, Mathiron et al 2017. And, alternatively, is there a coupling of the evolutionary forces shaping migration and dispersal, implying selective pressures that act jointly on morphological, physiological, and behavioral traits affecting the movement?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They raise interesting questions about the evolutionary pathways that contribute to the diversification of movement strategies in the wild (Cote et al 2017b): is dispersal only a by-product of the evolution of migratory movement providing temporary escape from the environmental constraints of the aquatic habitat (e.g. predation and drying up: Winandy et al 2015, Mathiron et al 2017. And, alternatively, is there a coupling of the evolutionary forces shaping migration and dispersal, implying selective pressures that act jointly on morphological, physiological, and behavioral traits affecting the movement?…”
Section: Discussionmentioning
confidence: 99%
“…before/after the reproductive period from/to overwintering and estivating terrestrial sites), and facultative habitat supplementation, resulting in breeding dispersal among ponds during the reproductive period and not considered as migratory events (Semlitsch 2008, Pittman et al 2014. Natal dispersal usually involves habitat complementation as gilled organisms leave water after metamorphosis (Mathiron et al 2017) whereas breeding dispersal can include both habitat complementation and supplementation depending whether the terrestrial phase is only used for movement across breeding patches or used for other activities such as estivation or overwintering. To date, few studies have shown that breeding pond characteristics may affect dispersal decision among ponds and result in condition-dependent dispersal (see for instance Cayuela et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, mixed models showed that climate change affected the metamorphic phenotype in the studied populations. Although drought events can affect populations of paedomorphs in other areas (Semlitsch and Gibbons 1985, Mathiron et al 2017, it is less likely the case in Montenegro because most ponds and lakes are very deep, making them permanent aquatic habitats. In contrast, high temperatures were associated with a decrease in the occurrence of the metamorphs, the terrestrially adapted phenotypes.…”
Section: Anthropogenic Pressures On Freshwater Habitats and Amphibiansmentioning
confidence: 99%
“…, Mathiron et al. ). Yet, a genetic basis of paedomorphosis was found in some species (Voss and Shaffer ) and constraining environments can promote metamorphosis over paedomorphosis across generations (Semlitsch and Wilbur ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation